El deteriorament del marc normatiu de les competències lingüístiques del personal sanitari a les Illes Balears. Els seus efectes sobre el règim tuïtiu de la llengua catalana - Ballester Cardell, Maria (Revista de Llengua i Dret, 2025)
Gairebé a punt de complir-se el quarantè aniversari de l’aprovació de la Llei 3/1986, de 29 d’abril, de normalització lingüística de les Illes Balears, continua molt viu el debat sobre el règim de capacitació lingüística del personal sanitari del Servei de Salut. Les successives revisions normatives sobre l’ús de les llengües oficials en aquest àmbit i la resposta judicial, tant respecte a l’establiment del requisit de coneixements de llengua catalana com a l’adopció de mesures potencialment regressives, són una mostra de les dificultats que comporta avançar cap a un marc jurídic estable que garanteixi adequadament els drets lingüístics dels usuaris en l’àmbit assistencial i sanitari. En aquest estudi s’analitzen les tensions provocades per les fluctuacions normatives que s’han produït en les darreres legislatures i la doctrina recent del Tribunal Constitucional en relació amb la rebaixa de les competències lingüístiques del personal sanitari del Servei de Salut de les Illes Balears. Aquestes circumstàncies, en conjunt, marquen una tendència regressiva i fan minvar el nivell de protecció de la llengua catalana a les Illes Balears. , Almost on the eve of the 40th anniversary of the approval of Law 3/1986, of 29 April, on the linguistic normalisation of the Balearic Islands, the debate on the language training regime for health service staff is still very much alive. The successive regulatory revisions on the use of the official languages in this field and the judicial response, with regard to both the requirement to know Catalan and the adoption of potentially regressive measures, are an example of the difficulties involved in moving toward a stable legal framework that adequately guarantees users’ language rights in the healthcare field. This study analyses the tensions caused by the regulatory fluctuations that have occurred in recent legislatures and the recent doctrine of the Constitutional Court in relation to the reduction in the level of language competence required by healthcare staff in the Balearic Islands Health Service. These circumstances, taken together, mark a regressive trend and lower the level of protection of the Catalan language in the Balearic Islands. , Casi a punto de cumplirse el cuadragésimo aniversario de la aprobación de la Ley 3/1986, de 29 de abril, de Normalización Lingüística de las Islas Baleares, continúa muy vivo el debate sobre el régimen de capacitación lingüística del personal sanitario del Servicio de Salud. Las sucesivas revisiones normativas sobre el uso de las lenguas oficiales en este ámbito y la respuesta judicial, tanto con respecto al establecimiento del requisito de conocimientos de lengua catalana como a la adopción de medidas potencialmente regresivas, son una muestra de las dificultades que comporta avanzar hacia un marco jurídico estable que garantice adecuadamente los derechos lingüísticos de los usuarios en el ámbito asistencial y sanitario. En este estudio se analizan las tensiones provocadas por las fluctuaciones normativas que se han producido en las últimas legislaturas y la reciente doctrina del Tribunal Constitucional en relación con la rebaja de las competencias lingüísticas del personal sanitario del Servicio de Salud de las Islas Baleares. Estas circunstancias, en conjunto, marcan una tendencia regresiva y disminuyen el nivel de protección de la lengua catalana en las Islas Baleares.

From Policy to Practice: A Qualitative Study on Reforms and Frontline Retention in Healthcare - Dubé, Anik; Collin, Stéphanie; Hakim, Jennifer; Johnson, Claire; Laforest, Marie-Ève; Landry, Michel H.; Lauzier, Martin (INQUIRY: The Journal of Health Care Organization, Provision, and Financing, 2025)
In Canada, healthcare reforms typically aim to improve the quality of care and access while making healthcare systems more efficient. These reforms have led to a 2-level healthcare system consisting of provincial and regional health authorities (RHAs). RHAs are responsible for providing and administering health services within specific territories. One of the 2 language-based RHAs in New Brunswick (NB) operates in French-speaking rural minority communities. This study explored key factors affecting the retention of nurses and physicians within a RHA operating in a language minority context. This descriptive qualitative study explored how macro-level decisions are experienced on the frontlines. Data were collected through semi-structured interviews with 21 physicians and 37 registered nurses, as well as 2 focus groups involving 20 key informants in managerial roles. Thematic analysis was used to identify key themes. Three main factors emerged: organizational accountability and frustration, local autonomy and contextual responsiveness, and a culture of openness and perceived loss of control. These factors are associated with policy changes that affect operational settings and resource distribution within the RHA and influence the retention of nurses and physicians. Stakeholders in health system reforms, including governments and RHAs, must recognize that policy adjustments can have direct implications on everyday care. Participants expressed a growing disconnect from decision-making hierarchies and a perceived loss of control. Both are seen as barriers to delivering quality care. Ensuring adequate support and resources for implementing system-level changes is key to fostering professional engagement and enhancing job satisfaction.

Apprentissage de l’offre active des services sociaux et de santé en français par module de simulation interprofessionnelle au bénéfice des francophones en situation minoritaire au Canada - Giroux, Isabelle; Savard, Jacinthe; Tyerman, Jane; Savard, Sébastien; Benoît, Josée; Kengneson, Cris-Carelle (Revista de Llengua i Dret, 2025)
Résumé La formation des futurs prestataires de soins à l’offre active (OA) des services sociaux et de santé (SSS) en français est essentielle pour permettre l’accès équitable à des services de qualité pour les francophones en situation minoritaire (FSM) au Canada. L’apprentissage par module de simulation interprofessionnelle est une avenue prometteuse à évaluer. L’objectif du présent travail est d’évaluer la satisfaction et l’efficacité perçue de l’apprentissage de l’OA des SSS en français à l’aide d’un module de simulation interprofessionnelle spécifique, le MODULE-IP-SIM-OA. En ce qui concerne la méthodologie, des stagiaires de programmes en SSS de l’Université d’Ottawa ont complété le dit module, suivi d’un débreffage synchrone et d’un questionnaire de rétroaction en ligne, entre mai et décembre 2023. Les 216 stagiaires issus de neuf disciplines ont rapporté des taux élevés de satisfaction et d’efficacité perçue concernant le MODULE-IP-SIM-OA et son débreffage. Cet apprentissage, jugé efficace par les stagiaires, pourrait avoir des retombées positives sur l’offre de services aux FSM afin d’atténuer les barrières linguistiques en santé. Resum La formació dels futurs professionals de la salut sobre l’oferta activa (OA) dels serveis socials i de salut (SSS) en francès és essencial per permetre un accés equitatiu a serveis de qualitat a les persones francòfones en situació minoritària (FSM) al Canadà. L’aprenentatge mitjançant un mòdul de simulació interprofessional és una via prometedora que cal explorar. L’objectiu d’aquest treball és avaluar el nivell de satisfacció i d’eficàcia percebuda de l’aprenentatge de l’OA dels SSS en francès amb l’ajuda d’un mòdul de simulació interprofessional específic, el MODULE-IP-SIM-OA. Pel que fa a la metodologia, diversos estudiants en pràctiques de programes de SSS de la Universitat d’Ottawa van completar aquest mòdul, seguit d’una sessió de debrífing síncrona i d’un qüestionari de valoració en línia, entre els mesos de maig i desembre de 2023. Els 216 estudiants, provinents de nou disciplines diferents, van aportar respostes que indiquen nivells alts de satisfacció i d’eficàcia percebuda en relació amb el MODULE-IP-SIM-OA i el debrífing posterior. Aquest aprenentatge, que els participants van considerar eficaç, podria tenir efectes positius en l’oferta de serveis als FSM per reduir les barreres lingüístiques en l’àmbit de la salut. Abstract Training future care providers in the active offer (AO) of social and health services (SHS) in French is essential for ensuring equitable access to quality services for Francophones in minority contexts (FMS) in Canada. Learning through an interprofessional simulation module is a promising approach that warrants evaluation. The purpose of this paper is to assess the satisfaction and perceived effectiveness of learning the AO of SHS in French using a specific interprofessional simulation module, the MODULE-IP-SIM-OA. Regarding methodology, between May and December 2023, trainees from SHS programs at the University of Ottawa completed this module, followed by a synchronous debriefing and an online feedback questionnaire. The 216 trainees from nine disciplines reported high levels of satisfaction and perceived effectiveness regarding the MODULE-IP-SIM-OA and its debriefing. This learning experience, considered effective by the trainees, could have positive impacts on service delivery to FMS and help reduce language barriers in healthcare. Resumen La formación de los futuros profesionales de la salud sobre la oferta activa (OA) de los servicios sociales y de salud (SSS) en francés es esencial para permitir un acceso equitativo a servicios de calidad a las personas francófonas en situación minoritaria (FSM) en Canadá. El aprendizaje mediante un módulo de simulación interprofesional es una vía prometedora que hay que explorar. El objetivo de este trabajo es evaluar el nivel de satisfacción y de eficacia percibida del aprendizaje de la OA de los SSS en francés con la ayuda de un módulo de simulación interprofesional específico, el MODULE-IP-SIM-OA. Con respecto a la metodología, varios estudiantes en prácticas de programas de SSS de la Universidad de Ottawa completaron este módulo, seguido de una sesión de debriefing síncrona y de un cuestionario de valoración en línea, entre los meses de mayo y diciembre de 2023. Los 216 estudiantes, provenientes de nueve disciplinas diferentes, aportaron respuestas que indican niveles altos de satisfacción y de eficacia percibida en relación con el MODULE-IP-SIM-OA y el debriefing posterior. Este aprendizaje, que los participantes consideraron eficaz, podría tener efectos positivos en la oferta de servicios a los FSM para reducir las barreras lingüísticas en el ámbito de la salud.

Les langues officielles et les travailleurs de la santé au Canada: Un portrait. - Ouellet-Léveillé, Bertrand; St-Amant, Gabriel (Statistique Canada, 2025)
Selon le site internet de Statistique Canada, ce rapport est offert sur demande

Official languages and health care workers in Canada: A portrait. - Ouellet-Léveillé, Bertrand; St-Amant, Gabriel (Statistics Canada, 2025)
Te web site states: The report Official languages and health care workers in Canada: A portrait, 2025 is available upon request. This analysis was prepared for Health Canada.

Health providers’ perceptions on language barriers in Catalonia’s public healthcare system - Rubio-Carbonero, Gema; Gil-Bardají, Anna (Revista de Llengua i Dret, 2025)
In this article, we present the results of an exploratory quantitative study on the situation of communication between healthcare staff in the Catalan public system and users with limited competence in the official languages of Catalonia. The study objective is to offer a comprehensive and empirically grounded overview of the current state of intercultural communication in the Catalan public health system, with and without the involvement of third-party mediation, as perceived by healthcare providers. Data were collected through a structured questionnaire administered to professionals engaged in direct patient care across public health centres in Catalonia, yielding a sample of 1 390 respondents. The findings underscore the high frequency and significant impact of language barriers in clinical encounters and highlight notable deficiencies in the resources currently available to address these challenges. , Aquest article presenta els resultats d’un estudi quantitatiu exploratori sobre la situació de la comunicació entre el personal sanitari del sistema públic català i els usuaris que tenen un coneixement limitat de les llengües oficials de Catalunya. L’objectiu de l’estudi és oferir una visió global i amb una base empírica de l’estat actual de la comunicació intercultural en el sistema públic de salut català –tant amb la mediació de tercers com sense– a partir de la percepció que en tenen els professionals sanitaris. Les dades es van recollir mitjançant un qüestionari estructurat administrat a professionals que treballen en l’atenció directa als pacients en centres públics de salut de Catalunya, que va permetre obtenir una mostra de 1.390 participants. Els resultats posen de manifest l’alta freqüència i el fort impacte de les barreres lingüístiques en les interaccions clíniques, així com mancances notables en els recursos disponibles actualment per afrontar aquests reptes. , Este artículo presenta los resultados de un estudio cuantitativo exploratorio sobre la situación de la comunicación entre el personal sanitario del sistema público catalán y los usuarios con un conocimiento limitado de las lenguas oficiales de Cataluña. El objetivo del estudio es ofrecer una visión global y con base empírica del estado actual de la comunicación intercultural en el sistema público de salud catalán –tanto con la mediación de terceros como sin ella– a partir de la percepción de los profesionales sanitarios. Los datos se recogieron mediante un cuestionario estructurado administrado a profesionales que trabajan en la atención directa al paciente en centros públicos de salud de Cataluña, con el que se obtuvo una muestra de 1.390 participantes. Los resultados ponen de manifiesto la elevada frecuencia y el fuerte impacto de las barreras lingüísticas en las interacciones clínicas, así como carencias notables en los recursos disponibles actualmente para afrontar tales desafíos.

French among Health Care Workers in Canada Outside Quebec, 2021 (Infographic) - Statistics Canada (2025)

French and English among Healthcare Workers in Quebec, 2021 (Infographic) - Statistics Canada (2025)

Le français chez les travailleurs et travailleuses de la santé au Canada hors Québec, 2021 (infographie) - Statistique Canada (2025)

Le français et l'anglais chez les travailleurs et travailleuses de la santé au Québec - 2021 (infographie) - Statistique Canada (2025)

Reporting on knowledge, attitudes, and behaviours of pharmacists regarding the active offer of French language health services in Ontario: A quantitative survey study - Timony, Patrick; Leone, Arielle; Caron, Carolanne; Giguère, Pierre; Thabet, Pierre; Gauthier, Alain; Waite, Nancy M.; Landry, Christine (Canadian Pharmacists Journal / Revue des Pharmaciens du Canada, 2025)
Background: Patient–provider language discordances can negatively affect the availability, accessibility, acceptability, and quality (AAAQ) of pharmacy services as described by the AAAQ framework. With nearly 600,000 residents of Ontario identifying French as their mother tongue, the active offer (AO) of French language pharmacy services should be provided, yet little is known about pharmacists’ familiarity and use of AO. Methods: Ontario pharmacists completed an online survey measuring their knowledge, attitudes, and behaviours (KAB) regarding the AO for French language services (FLS). Demographics, including ability to converse in French, were collected. KAB AO scores were calculated and compared using descriptive and inferential statistics. Results: A total of 360 pharmacists completed the survey. The majority (65.1%) practiced in a primary care setting, 21.1% spoke French, and 71.8% lived in an area where less than 10% of the population were Francophone. Overall, AO scores were highest for attitude (3.8/5) and lowest for behaviours (2/5) and knowledge (1.8/5). Most pharmacists (62.8%) indicated an interest in AO training. Discussion: Gaps in KAB regarding AO for FLS by Ontario pharmacists resemble those observed throughout the health care system. Further training is suggested to address the lack of knowledge regarding AO, particularly its proactive nature, as well as strategies for its implementation. Conclusion: Although most participating pharmacists demonstrated gaps in AO knowledge and behaviour, many had favourable attitudes toward the importance of AO in the pharmacy setting and agreed that further training would be needed to improve their KAB. Further, the AO can address all 4 elements of the AAAQ framework.

Un modèle de création de simulation virtuelle en langue française pour le curriculum canadien du baccalauréat en sciences infirmières - Tyerman, Jane; Bailey, Liana (Revue Francophone Internationale de Recherche Infirmière, 2025)
Bien que le Canada soit un pays officiellement bilingue, il serait nécessaire d’augmenter de façon significative le nombre de ressources éducatives de bonne qualité en français, pour les étudiants en sciences infirmières. La simulation virtuelle est un outil pédagogique apprécié pour sa capacité d’être à la fois accessible, flexible et sécuritaire. Le but de cet article est de détailler le processus de création de simulations virtuelles en langue française utilisée pour le curriculum canadien du baccalauréat en sciences infirmières. Cet article propose un modèle en quatre étapes soutenant la création de simulations virtuelles en français : la rédaction/conversion, l’évaluation par les pairs, la revue finale et la publication. Le produit final est un référentiel d’outils pédagogiques permettant le renforcement de la formation des infirmières. Summary Although Canada is an officially bilingual country, there is still a need to significantly increase the number of good-quality, French-language educational resources for nursing students. Virtual simulation is a pedagogical tool that is appreciated for its ability to be accessible, flexible and safe. The aim of this article is to detail the process used to create French-language virtual simulations for the Canadian baccalaureate nursing curriculum. This article proposes a four-stage model supporting the creation of French-language virtual simulations: writing/conversion, peer review, final review, and publication. The final product is a repository of pedagogical tools to reinforce nursing education.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.

Pratique # 25 : Accès éQUITÉ : Simplifier l’accès aux services de santé en français (Société Santé en français) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Presente, pasado y (sobre todo) futuro de la atención sanitaria en euskera [Present, past and (above all) future of healthcare in Basque] - Zarate Sesma, Jon; Montes, Aitor (Revista de Llengua i Dret, 2025)
Resumen La normalización de la atención sanitaria sería ofrecer una atención integrada basada en la evidencia y centrada en el usuario (paciente), lo que pasa por una atención en el idioma de elección del usuario. Para la consecución de dicha normalización, y teniendo en cuenta la complejidad del sistema sanitario centrado en el usuario, es necesario poner en marcha políticas que apuesten por el impulso de la conciencia lingüística entre los profesionales sanitarios y ofrecer estrategias para asegurar la asistencia sanitaria integral en euskera. Es imprescindible aprobar un nuevo decreto que reemplace el Decreto 67/2003 y que exija como mínimo el nivel C1 en euskera para el ejercicio de la profesión sanitaria. Del mismo modo, habría que registrar el idioma de elección del usuario a través de la oferta activa, impulsar los circuitos sanitarios en euskera (con la identificación de los servicios y profesionales euskaldunes) y poner en marcha la historia clínica en euskera. Resum La normalització de l'atenció sanitària seria oferir una atenció integrada basada en l'evidència i centrada en l'usuari (pacient), la qual cosa passa per una atenció en l'idioma d'elecció de l'usuari. Per a la consecució de l'esmentada normalització, i tenint en compte la complexitat del sistema sanitari centrat en l'usuari, cal posar en marxa polítiques que apostin per l'impuls de la consciència lingüística entre els professionals sanitaris i oferir estratègies per assegurar l'assistència sanitària integral en eusquera. És imprescindible aprovar un nou decret que reemplaci el Decret 67/2003 i que exigeixi com a mínim el nivell C1 d’eusquera per a l'exercici de la professió sanitària. Així mateix, caldria registrar l'idioma d'elecció de l'usuari a través de l'oferta activa, impulsar els circuits sanitaris en eusquera (amb la identificació dels serveis i professionals bascoparlants) i posar en marxa la història clínica en eusquera. Abstract Healthcare normalisation should involve evidence-based and user (patient)-centred integrated care, provided in the user’s language of choice. To achieve this normalisation, and bearing in mind the complexity of the user-centred healthcare system, it is necessary to implement policies that promote language awareness among healthcare professionals and to offer strategies to ensure comprehensive healthcare in Basque. It is essential to pass a new decree to replace Decree 67/2003, requiring a minimum level of C1 in Basque to work as a healthcare professional. The user’s language of choice should also be recorded by the healthcare system, promoting healthcare circuits in Basque (identifying services available in Basque and Basque-speaking professionals) and making medical records available in Basque. Laburpena Osasun-arretaren normalizazioa ebidentzian oinarritutako eta erabiltzailearengan (pazientearengan) zentratutako arreta integratua eskaintzea litzateke, hau da, nahitaez erabiltzailearen aukerako hizkuntzan. Osasun-sistemaren konplexutasunak beharrezkoa egiten du giza kapitalean oinarritutako kultura-aldaketa: hizkuntza-kontzientzia duten langile ekintzaileak. Eztabaida eta paradigma berriak, diskurtso berria, erabiltzailearengan kokatu behar da, eta ez medikuarengan. Etorkizuna, neurri handi batean, osasun-profesionalen artean hizkuntza-kontzientzia sustatzearen aldeko apustua egiten duten politiken mende dago, bai eta osasun-arreta integrala euskaraz bermatzeko estrategiak eskaintzen dituztenen mende ere. Ezinbestekoa da dekretu berri bat onartzea, 67/2003 Dekretua ordeztuko duena eta lanbide sanitarioan jarduteko gutxienez euskarazko C1 maila eskatuko duena. Era berean, erabiltzaileak arretarako aukeratzen duen hizkuntza eskaintza aktiboaren bidez erregistratu beharko litzateke, osasun-zirkuituak euskaraz sustatu beharko lirateke (zerbitzu eta profesional euskaldunak identifikatuta) eta historia klinikoa euskaraz abiarazi beharko litzateke.